Artificial Intelligence and Student Learning in Higher Education: A Qualitative Exploration from District Gwadar - Sajeela Basheer; Rabia Aslam (Research Journal of Psychology, 2025)
The transformative possible of artificial intelligence (AI) in humanizing university students’ academic performance is discovered in this qualitative study. The study suggestions a thorough inspection of how AI-powered technologies support learning and affect students’ academic results by using in-person interviews as a data gathering method. The results show that artificial intelligence has many advantages, such as cost-effective solutions, individualized learning experiences, and effective information dispensation. But the study also exposes issues with belief on artificial intelligence, its drawbacks, and the requirement of careful integration. This study is main because it adds to the recent discussion about using artificial intelligence to maximize the usefulness of student learning. By using the knowledge collected from this study, higher education shareholders, educators, and officials may better apply artificial intelligence’s potential to develop more efficient, exciting, and student-centered knowledge situations. To exploit the profits of artificial intelligence in open-minded education, it is suggested that educators and councils carefully integrate AI-powered outfits into university curricula, supplementing traditional teaching methods.